2023
DOI: 10.51507/j.jams.2023.16.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Management of Endodontic Emergencies: a Review

Abstract: Root canal treatment (RCT) employed for painful endodontic conditions like apical periodontitis and irreversible pulpitis is associated with a high incidence of postoperative pain. Pharmacological management for this purpose is effective, but not entirely free from side effects and in some cases may fail to provide adequate relief. Furthermore, concerns have been raised regarding the transmission of coronavirus disease-2019 (COVID-19) as a result of the aerosols generated and prolonged chair side time required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…In that review, the authors evaluated the current evidence for the addition of acupuncture in endodontics and its potential role in emergency pain relief. 11 Five studies met the established criteria and reported the beneficial effects of acupuncture in reducing the failure of nerve block in patients with irreversible pulpitis, and in controlling both intraoperative and postoperative pain after root canal treatment.…”
Section: Dentistrymentioning
confidence: 99%
“…In that review, the authors evaluated the current evidence for the addition of acupuncture in endodontics and its potential role in emergency pain relief. 11 Five studies met the established criteria and reported the beneficial effects of acupuncture in reducing the failure of nerve block in patients with irreversible pulpitis, and in controlling both intraoperative and postoperative pain after root canal treatment.…”
Section: Dentistrymentioning
confidence: 99%
“…A few studies have explored its adjunctive role with local anesthesia and reported that it can improve the efficacy of local anesthesia when administered as a nerve block. It also helped calm the patients, reducing their apprehension and minimizing the need for oral analgesics, which can lead to other side effects [ 55 ]. Despite the promising results of acupuncture in managing endodontic pain, there are notable challenges and limitations to its wider adoption in dental practice.…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, a systematic review of randomized controlled clinical trials has concluded that the effectiveness of phototherapy in reducing PEP after RCT remains debatable. To better understand the true potential for success, more randomized controlled trials involving laser interventions need to be conducted following established guidelines and parameters [ 54 - 55 ]. There is a glimmer of hope in research that suggests lasers have been therapeutically used for various applications, including direct irradiation of root canals, adjunctive use with irrigants in combination with photosensitizers for antimicrobial photodynamic therapy, and pain management through photobiomodulation [ 57 ].…”
Section: Reviewmentioning
confidence: 99%